Health Implications of Building Retrofits: Evidence from a Population-Wide Weatherization Program - Steffen Künn; Juan Palacios (Institute of Labor Economics (IZA), 2023)
What is the impact of housing upgrades on occupant health? Although economists and policymakers are certain about the health implications of housing upgrades, empirical evidence is largely missing or else only based on small-scale experiments in developing countries. This study provides the first population-representative quasi-experimental estimates based on a large-scale refurbishment program that renovated half of the East German housing portfolio in the aftermath of German reunification. During the 1990s, the German government devoted significant financial resources to upgrading the insulation and heating systems of over 3.6 million dwellings in East Germany. We link the renovations to individual demand for the healthcare of occupants using the German Socio-Economic Panel (SOEP) as well as administrative records of universal hospital admissions in Germany. Exploiting the staggered roll-out of the renovation program, our results show that an improvement in housing quality enhances the health of vulnerable age groups. Evidence from hospital records suggests that reductions in hospitalization were due to a lower risk of cardiovascular problems for older individuals (45 years or older) which were mainly driven by days with extremely hot and cold ambient temperatures. Our findings have strong policy implications and can enrich the cost-benefit analysis of public investments in weatherization programs.
Keywords: H54; I18; R21; R23; R38; 330; housing quality; renovation program; health